The Economy of Inland Rejang Bengkulu in the Early 20th Century - Hidayat, Taufik (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to examine the Rejang plateau region which became a new economic center in Bengkulu in the early 20th century. This research is a historical research including heuristics, source criticism, interpretation, and historiography. This research uses an economic approach, data collection techniques in this research through literature studies such as tracing archives of colonial government annual reports and literature studies. The results of this study show that the Rejang region became the economic center in Bengkulu because the Rejang region was chosen as the location for the opening of private companies engaged in plantations and mining. Rejang was chosen as the location of private companies in Bengkulu because it has potential, especially favorable geographical factors. The operation of private companies in Rejang had an impact on the construction of increasingly massive roads from the interior region to the city of Bengkulu. Road construction in Rejang has opened up new economic opportunities for the community, such as the formation of markets or small towns and the emergence of new employment opportunities.